Emergence, growth, and quality of Calycophyllum spruceanum plants produced in different containers and substrates - Guerra Arévalo, Wilson Francisco (2024)
The growing demand for Calycophyllum spruceanum is causing strong pressure on natural populations due to anthropogenic activities. For this reason, it is urgent to develop propagation technologies and production of plants for reforestation activities and establishment of forest plantations for their use and conservation. The objective of this study was to determine the effect of different substrates and containers on the emergence and growth of C. spruceanum. For this purpose, two experiments were conducted. In the first, four substrates were tested to evaluate seedling emergence, while in the second, the growth and quality of plants in different containers and substrates were determined. The maximum emergence values of 62.3%, emergency speed index (ESI) of 2.2, and mean emergence time of 29.9 were determined using a combination of carbonized rice husk (CRH), chicken manure, and decomposed sawdust in a 1:1:1 ratio. The combination of the plastic bag container with CRH and poultry manure in a 1:1 ratio. Substrate gave the best results for total dry biomass (27.40), lignification index (0.19), robustness index (5.56), and Dickson’s quality index (3.26). Therefore, the use of CRH, poultry manure, and decomposed sawdust in a 1:1:1 ratio is recommended for seedling emergence. Similarly, the use of a plastic bag-type container and the substrate CRH and chicken manure in a 1:1 ratio is recommended for the production of C. spruceanum plants.